2005
DOI: 10.1111/j.1365-3180.2005.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential translocation of paraquat in paraquat‐resistant populations of Hordeum leporinum

Abstract: Two populations of Hordeum leporinum have evolved resistance to paraquat within a small area in central Tasmania, Australia. One population (THL1) was more than 80-fold resistant to paraquat when treated in winter, compared with a susceptible population (THL4) collected nearby, whereas the other population (THL2) was only 19-fold resistant. Translocation of paraquat was examined in all three populations at warm and cool temperature regimes. Herbicide was applied to a basal section of the second leaf of plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
2
17
0
1
Order By: Relevance
“…1; Table 1). Temperature is a major factor affecting the plant response to paraquat (Preston et al 2005;Purba et al 1995;Yu et al 2004). Similarly here, we observed higher paraquat efficacy and greater differential sensitivity to paraquat between the unselected parental and glyphosate-selected plants grown at lower temperature ( Table 1).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…1; Table 1). Temperature is a major factor affecting the plant response to paraquat (Preston et al 2005;Purba et al 1995;Yu et al 2004). Similarly here, we observed higher paraquat efficacy and greater differential sensitivity to paraquat between the unselected parental and glyphosate-selected plants grown at lower temperature ( Table 1).…”
Section: Resultssupporting
confidence: 63%
“…Figure 3a, b, c from Busi and Powles 2009 observed shift was well beyond the expected baseline variation for herbicide sensitivity to paraquat in unselected populations of L. rigidum or other species (Yu et al 2004;Preston et al 2005;Yu et al 2007). Selection experiments repeated in time and place by conducting one experiment under controlled growth room conductions and one in field conditions showed the same evolution of glyphosate resistance and concomitant reduced paraquat sensitivity (Tables 1 and 2).…”
Section: Paraquat Reduced Sensitivity Of Outdoor Field-grown Plantsmentioning
confidence: 63%
“…Reduced translocation was reported as the cause of resistance to paraquat in two populations of Hordeum leporinum [7]. The inability to translocate paraquat out of the treated leaves was verified with the use of 14 C-labeled paraquat comparing the two resistant populations with a susceptible one, all from Australia.…”
Section: Restriction Of Herbicide Movement In Resistant Weedsmentioning
confidence: 93%
“…It was concluded that the resistance to paraquat was the result of the reduced herbicide translocation out of the treated leaves [76]. One can suppose that also in this species herbicide sequestration may have been the primary cause for the altered long-distance transport.…”
Section: Nontarget-site Resistance By Enhanced Metabolic Detoxificationmentioning
confidence: 99%